?????? ??????? ????? "??????? ???????" ?? ????? ????? ????? - Farid Qomaruddin (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2018)
Al-Musthofawiyah senior high school is a private Islamic education institution located in Palang-Tuban. This institution pays attention to the Arabic grammar of science which among them are the grammar of Nahwu. However, Nahwu's grammar of learning were still considered quite difficult to be understood. Media is very instrumental in supporting the language skills of students in institutions and schools, because media is an important element that can affect the learning activeness of students. In this article the author conducted a study that aims to determine the effectiveness of the use of the media "Nahwu Mapping" in the learning of nahwu grammar in this school. This study uses a qualitative approach with a type of classroom action research